Analysis of Education, Work Environment, and Job Satisfaction Influencing Paramedic Behavior in Indonesian Hospitals - Vermona Marbun; I Nyoman Ehrich Lister; Linda Chiuman; Ermi Girsang (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
This research investigates the impact of education, work environment, and job satisfaction on the behavior of paramedics in Indonesian hospitals. A quantitative approach was employed, utilizing survey data collected from paramedics across Indonesia. The study aims to identify key factors influencing paramedic behavior, offering valuable insights for hospital management to enhance healthcare service quality. Multiple regression analysis was used to test the hypotheses. The results indicated that education (β = 0.25, p < 0.05), work environment (β = 0.32, p < 0.05), and job satisfaction (β = 0.40, p < 0.05) significantly and positively influence paramedic behavior. Additionally, education positively impacts both the work environment (β = 0.35, p < 0.05) and job satisfaction (β = 0.42, p < 0.05). These findings underscore the importance of continuous professional development, a conducive work environment, and high job satisfaction in promoting positive paramedic behavior and improving patient care in Indonesian hospitals.